Dampak Penyelenggaraan Merdeka Belajar Kampus Merdeka Kepada Mahasiswa Di Fakultas Hukum Universitas Al Azhar Indonesia - Zuhad Aji Firmantoro; Suartini Supendi (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
The Merdeka Learning-Independence Campus Program in Indonesian is abbreviated as MBKM. MBKM, which was initiated by the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia has been running for one year. The aim is to increase the competency of graduates so that they are better prepared to respond to the needs of the times. This research was conducted with the aim of knowing more accurately the impact of holding the MBKM program on students at the Faculty of Law, University of Al Azhar Indonesia. The research method used was descriptive statistics and Spearman’s coefficient by taking a sample of 340 students from a total population of 600 students. The sampling technique was carried out by using random sampling, i.e., taking samples from members of the entire population at random, without regard to the existing strata in the population. The results of this study show that, first, students interest in participating in the MBKM program is in line with their level of knowledge of MBKM. After conducting a survey of 340 students out of 600, it was found that 93 students were interested in joining the MBKM program. Second, the small number of students participating in MBKM (93 students) was caused by technical selection factors, which limited the MBKM quota. Third, the problems faced by blended students are not resolved, causing a small number of blended students to join MBKM Keywords – MBKM, FH UAI, Students